Centre of pressure changes during stance but not during gait in young women after alcohol intoxication - Marta Gimunová; Michal Bozděch; Jan Novák (PeerJ, 2023)
Background Women are underrepresented in research focused on alcohol (e.g., Brighton, Moxham & Traynor, 2016; DOI 10.1097/JAN.0000000000000136) despite the changing patterns of alcohol consumption, which has been increasing in women in recent decades. The purpose of this study was to analyse the relationship between habitual alcohol consumption and centre of pressure (CoP) parameters during stance and gait while intoxicated by alcohol. Methods Thirty women (24.39 ± 2.93 years) participated in this study. All participants were asked to answer the AUDIT questionnaire. Stance and gait analysis were repeated under two conditions on a Zebris platform (FDM GmbH; Munich, Germany): when the participants were sober (0.00% breath alcohol concentration, BrAC) and when they were in an intoxicated state (0.11% BrAC). Participants were divided by their AUDIT score into a low-risk alcohol consumption group (n = 15; AUDIT score: 3 to 6) and a hazardous alcohol consumption group (n = 15; AUDIT score: 7 to 13). Results No statistical difference was observed in stance and gait parameters when comparing the low-risk and hazardous groups under 0.00% BrAC and 0.11% BrAC conditions. A statistically significant difference was observed when comparing 0.00% BrAC and 0.11% BrAC conditions within each group. This significant difference was found in CoP path length and CoP average velocity during quiet stance. However, no statistically significant differences were observed in CoP parameters during gait. An alcohol intoxication of 0.11% BrAC was not sufficient to cause statistically significant impairments in butterfly parameters of gait.